Whole genome re-sequencing reveals adaptation prior to the divergence of buffalo subspecies - Rafiepour, M.; Ebrahimie, E.; Vahidi, M.F.; Salekdeh, G.H.; Niazi, A.; Dadpasand, M.; Liang, Dong; Si, Jingfang; Ding, Xiangdong; Han Jianlin; Zhang, Yi; Qanbari, S. (Oxford University Press, 2021)
The application of high-throughput genotyping or sequencing data helps us to understand the genomic response to natural and artificial selection. In this study, we scanned the genomes of five indigenous buffalo populations belong to three recognized breeds, adapted to different geographical and agro-ecological zones in Iran, to unravel the extent of genomic diversity and to localize genomic regions and genes underwent past selection. A total of 46 river buffalo whole genomes, from West and East Azerbaijan, Gilan, Mazandaran, and Khuzestan provinces, were resequenced. Our sequencing data reached to a coverage above 99% of the river buffalo reference genome and an average read depth around 9.2× per sample. We identified 20.55 million SNPs, including 63,097 missense, 707 stop-gain, and 159 stop-loss mutations that might have functional consequences. Genomic diversity analyses showed modest structuring among Iranian buffalo populations following frequent gene flow or admixture in the recent past. Evidence of positive selection was investigated using both differentiation (Fst) and fixation (Pi) metrics. Analysis of fixation revealed three genomic regions in all three breeds with aberrant polymorphism contents on BBU2, 20, and 21. Fixation signal on BBU2 overlapped with the OCA2-HERC2 genes, suggestive of adaptation to UV exposure through pigmentation mechanism. Further validation using resequencing data from other five bovine species as well as the Axiom Buffalo Genotyping Array 90K data of river and swamp buffaloes indicated that these fixation signals persisted across river and swamp buffaloes and extended to taurine cattle, implying an ancient evolutionary event occurred before the speciation of buffalo and taurine cattle. These results contributed to our understanding of major genetic switches that took place during the evolution of modern buffaloes.